2003
DOI: 10.1016/s0378-4371(02)01688-6
|View full text |Cite
|
Sign up to set email alerts
|

Continuum percolation of simple fluids: energetic connectivity criteria

Abstract: During the last few years, a number of works in computer simulation have focused on the clustering and percolation properties of simple fluids based in an energetic connectivity criterion proposed long ago by T.L. Hill [J. Chem. Phys. 23, 617 (1955)]. This connectivity criterion appears to be the most appropriate in the study of gas-liquid phase transition. So far, integral equation theories have relayed on a velocity-averaged version of this criterion. We show, by using molecular dynamics simulations, that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Note that the water-rich branch of the coexistence curve may be located in a similar way by using an appropriate criterion for the connectivity of the solute molecules. [6][7][8] The proposed scheme allows one to avoid simulations with two coexisting phases in one simulation box (and so, with an explicit interface). Alternatively, MC or molecular dynamics simulations in an NPT-or NVT-ensemble could be used, allowing one to estimate the location of the liquid-liquid coexistence curve of an aqueous solution, when all other available methods (simulations in the Gibbs ensemble in particular) fail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the water-rich branch of the coexistence curve may be located in a similar way by using an appropriate criterion for the connectivity of the solute molecules. [6][7][8] The proposed scheme allows one to avoid simulations with two coexisting phases in one simulation box (and so, with an explicit interface). Alternatively, MC or molecular dynamics simulations in an NPT-or NVT-ensemble could be used, allowing one to estimate the location of the liquid-liquid coexistence curve of an aqueous solution, when all other available methods (simulations in the Gibbs ensemble in particular) fail.…”
Section: Discussionmentioning
confidence: 99%
“…The percolation threshold should coincide with the thermodynamic critical point of Ising magnets and pure fluids, when the proper criterion for a physical cluster is used. 5 Indeed, this was observed for a Lennard-Jonnes fluid, when two molecules are considered as connected, if the magnitude of the (negative) potential energy exceeds their relative kinetic energy 6,7 (see ref. 8 for a recent review).…”
Section: Introductionmentioning
confidence: 93%
“…Interactions between nodes are represented as an edge, using appropriate criteria that represent when two nodes have a sufficiently strong interaction. An edge criterion may be defined geometrically or energetically (or with an additional temporal condition , ).…”
Section: Introductionmentioning
confidence: 99%
“…10 Interactions between nodes are represented as an edge, using appropriate criteria that represent when two nodes have a sufficiently strong interaction. An edge criterion may be defined geometrically 11 or energetically 12 (or with an additional temporal condition 13,14 ). Note that a wide variety of graph topologies can be observed in chemical systems, and as such, it is important that any algorithm is robust to such variations and can further describe the aforementioned heterogeneity across different scales.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This function verifies also an OZ like relationship. In a previous paper 25 (thereafter denoted as I) we applied our general theory to study the complete HE criterion for the same model fluid considered by Coniglio et al 14 under the VA criterion. We also used the same simple closure relation proposed by Coniglio et al More recently, we have reported 26 the solution of our generalized connectedness OZ type relation for a Lennard-Jones fluid closed with a connectedness Percus-Yevick (PY) condition.…”
Section: Introductionmentioning
confidence: 99%